Soil Quality Analysis for Dryland Agriculture with Variation of Fertilization and Plant Rotation in Argomulyo District, Salatiga City - Nurmaya, Eka; Fianti, Fianti; Yulianti, Ian (Physics Communication, 2022)
The study aim is to analyze soil quality for dryland agriculture with variations in fertilization and plant rotation in Argomulyo sub-district, Salatiga city. This study took samples on dryland agricultural land in Ledok Village by taking sample points using random sampling with a cluster sampling pattern by dividing them into 4 clusters. The Step of the research are field and laboratory observation to know the soil pH and moisture, also to determine the soil value and cation test, respectively. Next is the interview step to know the effect of fertilization and plant rotation variation. This research uses quantitative description analysis techniques. Based on the field observation was obtained the cluster 2 has pH value around 6.5 in the category slightly acidic. Then, for cluster 1,3, and has 4 neutral pH category in the range 6.6 – 7.5. The humidity of clusters in the dry category is in the range of 0 - 30%. Laboratory observation shows cluster 3 has a lower resistance around 8.1KW and has the best cation exchange capacity (CEC) test compared with other clusters. Based on the results of interviews, cluster 2 received organic fertilization and crop rotation occurred. Clusters 1 and 4 have not received any planting activity since October 2020. Meanwhile, fertilization in cluster 3 uses inorganic fertilizers. So Cluster 2 soil quality is better than the other three clusters due to organic fertilization and plans rotation so that the soil nutrients become stable. Cluster 1 has poor soil quality due to variations in inorganic fertilization, neglecting the soil, and being planted Manihot esculenta which impacted the reduction in the amount of nitrogen and phosphorus in the land.